Simple fiber optic sensor based on tapered fiber for aliphatic alcohol detection - Pang, S.W.; Yang, H.Z.; Harun, Sulaiman Wadi (INOE Publishing House, 2011)
A simple fiber optic sensor based on a tapered fiber is demonstrated to detect aliphatic alcohols such as methanol, ethanol, 1-propanol and 2-propanol. The change of the refractive index in the evanescent field in the tapering region of the fiber due to an aliphatic alcohol varies the output power. The optimum radius of tapered fiber core is theoretically found to be approximately 282 mu m. It is observed that increasing of alkyl substituent of primary aliphatic alcohol from C = 1 to C = 3 significantly decreases the output intensity of light that is transmitted through the tapered fiber. The output intensity increases slowly as the concentration increases from 10% to 50%. However, the intensity increases drastically as the concentration is increased from 50% to 100% especially for the methanol, which has a lower alkyl substituent (C = 1). The sensitivities of the tapered plastic fiber for 2-propanol, ethanol and methanol detections are obtained at 0.911, 1.046 and 5.234, respectively.